2017
DOI: 10.1177/1947603516686144
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression in Infrapatellar Fat Pad–Derived Mesenchymal Stem Cells in Osteoarthritis

Abstract: Aim In the osteoarthritis (OA) disease, all structures of the joint are involved. The infrapatellar Hoffa fat pad is rich in macrophages and granulocytes, which also represents a source of adipose mesenchymal progenitor cells (ASC) cells. In our study, we analyze how OA affects the ability of ASC-derived from Hoffa's fat pad to differentiate into chondrocytes. Material and methodology We took knee Hoffa's pad samples and adipose tissue from the proximal thigh from 6 patients diagnosed with severe OA and from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(34 reference statements)
1
13
0
1
Order By: Relevance
“…Since the sixties, it has long be known that SF from arthritic patients of various conditions, including OA, contains cells capable of in vitro proliferation, but their phenotypic characterization and multipotentiality were demonstrated in 2004 [ 25 ]. Their origin has been debated: blood irrigation, shedding from synovium [ 26 ], especially type B synovial lining, disrupted superficial cartilage layer [ 27 ], subchondral bone, infra-patellar pad [ 28 ]. For a decade, the presence of SF-MSCs in normal SF, increasing in early human OA, has been demonstrated [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the sixties, it has long be known that SF from arthritic patients of various conditions, including OA, contains cells capable of in vitro proliferation, but their phenotypic characterization and multipotentiality were demonstrated in 2004 [ 25 ]. Their origin has been debated: blood irrigation, shedding from synovium [ 26 ], especially type B synovial lining, disrupted superficial cartilage layer [ 27 ], subchondral bone, infra-patellar pad [ 28 ]. For a decade, the presence of SF-MSCs in normal SF, increasing in early human OA, has been demonstrated [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation of this peculiar chondrogenic commitment may be the physio-pathological microenvironment of the SF-MSCs used herein; all harvested in end-stage OA knees undergoing total knee joint replacement. In degenerative conditions, there is mainly a catabolic environment with a significant increase of TNFα and a significant decrease of TGF-ß1 [ 28 ]. During OA, synovitis causes hypoxia [ 47 ], hypercapnia, and acidity in synovial fluid [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The osteogenic differentiation potential of IPFP-ASCs is stronger in rheumatoid arthritis than in osteoarthritis, which may be related to tissue necrosis factor-α (TNF-α) [31]. Osteoarthritis can affect the chondrogenic differentiation potential of IPFP-ASCs [32]. The decreased chondrogenic differentiation potential of IPFP-ASCs may be associated with the downregulation of TGF-β gene expression in osteoarthritis [33].…”
Section: Effects Of Different Physiological Conditions On Proliferatimentioning
confidence: 99%
“…In addition, there are studies on IPFP-ASC differentiation at gene level. Bravo et al [32] have found that during IPFP-ASC chondrogenic differentiation, the expressions of PTFR and MMP13 are similar between the patients with knee osteoarthritis and the individuals with healthy knees, but the expressions of OPG, FGF2, TGF, and MMP3 are significantly lower in the patients with knee osteoarthritis than in the individuals with healthy knees.…”
Section: Differentiationmentioning
confidence: 99%
“…жировое тело склонно к изменению своей конфигурации при движениях в коленном суставе, тем самым обеспечивая механическую амортизацию и облегчая распределение синовиальной жидкости [10,11]. Диагностика изменений объема и структуры жировой клетчатки важна ввиду взаимосвязи её патологии с болевым синдромом в переднем отделе коленного сустава, а также возможной взаи-мосвязи с ранним формированием остеоартроза [12,13].…”
Section: Introductionunclassified